2012
DOI: 10.1371/journal.pone.0039101
|View full text |Cite
|
Sign up to set email alerts
|

3q26 Amplification Is an Effective Negative Triage Test for LSIL: A Historical Prospective Study

Abstract: BackgroundWomen with low grade squamous intraepithelial lesions (LSIL) at cervical cancer screening are currently referred for further diagnostic work up despite 80% having no precancerous lesion. The primary purpose of this study is to measure the test characteristics of 3q26 chromosome gain (3q26 gain) as a host marker of carcinogenesis in women with LSIL. A negative triage test may allow these women to be followed by cytology alone without immediate referral to colposcopy.Methods and FindingsA historical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…The current study data regarding ICN of TERC genes in normal samples (2%), LSIL (31%) specimens, and HSIL (85%) specimens were comparable to those in the literature . This is also in keeping with previous reports, in which an ICN of TERC genes improved the sensitivity for the detection of underlying high‐grade lesions in patients with LSIL . According to the recent study by Chen et al, TERC analysis showed a higher sensitivity (90%) and specificity (89.6%) than conventional cytology (sensitivity: 84% and specificity: 64.3%) for the detection of ≥CIN2 lesions .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The current study data regarding ICN of TERC genes in normal samples (2%), LSIL (31%) specimens, and HSIL (85%) specimens were comparable to those in the literature . This is also in keeping with previous reports, in which an ICN of TERC genes improved the sensitivity for the detection of underlying high‐grade lesions in patients with LSIL . According to the recent study by Chen et al, TERC analysis showed a higher sensitivity (90%) and specificity (89.6%) than conventional cytology (sensitivity: 84% and specificity: 64.3%) for the detection of ≥CIN2 lesions .…”
Section: Discussionsupporting
confidence: 89%
“…This so‐called stage differentiation (ie, the discrimination between cervical lesions of different grades using TERC assessment) has been confirmed in several studies . These previous publications assessing the value of TERC assessment in cervical cytology are listed in Table . This table illustrates that the evaluation criteria differ greatly among the studies (eg, the number of evaluated cells may range between 25 cells and 4996 cells).…”
Section: Discussionmentioning
confidence: 70%
“…The percentage of successfully hybridized samples was 100% in our study, considerably higher than in other studies [30,31,32,33]. In keeping with previous studies, we found a significant correlation (95%) between the HPV-DNA test and hTERC FISH.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies postulated the essential role of 3q26 during the progression of cervical lesions to invasive cancer [24], but the application of molecular techniques able to identify hTERC gene amplification in a clinical setting is still evolving [29,30,31,32,33]. Our goal was to evaluate 3q26 hTERC FISH analysis on liquid-based cervical samples, in order to establish its accuracy as a predictive test and its feasibility for routine application.…”
Section: Discussionmentioning
confidence: 99%
“…Many other triage methods for the cytological diagnoses of LSILs have been reported, including testing for specific oncogenic HPV types such as type 16 [10], HPV mRNA testing [11], 3q26 gain fluorescence in-situ hybridization testing [12], and measuring integration and quantifying markers of cell cycle aberration such as p16ink4a alone or in combination with Ki67 immunostaining [13,14]. Among these methods, the use of p16ink4a immunostaining has been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%